Analytical and Experimental Studies of Double Elastic Steel Sheet (DESS) Vibration Energy Harvester System - Yi-Ren Wang; Ming-Syun Wong; Bo-Yan Chen (Energies, 2020)
This study provides a double elastic steel sheet (DESS) piezoelectric energy harvester system, in which the vibration generated by the deformation and clap of two elastic steel sheets is assisted by a piezo patch to generate electric energy. The system is combined with energy storage equipment to propose a complete solution forgreen energy integration. This study buildsexperimentallyon the model of the proposed system to explore its voltage, power output and energy collection efficiency. This study also builds atheoretical model of a nonlinear beam with the piezo patch, including the piezoelectric coupling coefficient and current equation. This nonlinear problem is analyzed by the method of multiple scales (MOMS). The system frequency response wasobserved using fixed points plots. The perturbation technique and numerical method wereused to mutually validate the experimental results; the concept of DESS vibration energy harvester (DESS VEH) is proved feasible. In order to prolong the lifetime of the clapping of DESS piezo patch, a camber protector design is proposed. The findings show that the power-generating effect is best when the piezo patch is placed at the peak of the third mode of the DESS system, and the high camber protector is used to generate electric energy.